2020
DOI: 10.1093/cid/ciaa358
|View full text |Cite
|
Sign up to set email alerts
|

Isavuconazole as Primary Antifungal Prophylaxis in Patients With Acute Myeloid Leukemia or Myelodysplastic Syndrome: An Open-label, Prospective, Phase 2 Study

Abstract: Abstract Background Mold-active primary antifungal prophylaxis (PAP) is routinely recommended in neutropenic patients with newly diagnosed acute myeloid leukemia (AML) or high-risk myelodysplastic syndrome (MDS) undergoing remission-induction chemotherapy (RIC). Isavuconazole (ISAV) is an extended spectrum mold-active triazole and has superior tolerability and fewer significant drug–drug inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
46
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(60 citation statements)
references
References 38 publications
11
46
2
Order By: Relevance
“…The clinical phase III trial SECURE found the majority of s-ISZ measurements were within the range of 1–7 mg/L [ 23 ]. The median value in the present study was 4.3 mg/L and well within that range, the same as in other studies [ 7 , 8 , 9 , 12 , 17 , 24 , 25 , 26 ]. In the present study, the majority of the s-ISZ measurements were also within the recommended range, but for VRZ a third of TDM measurements were outside the recommended range, which is also in accordance with the literature [ 27 ].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The clinical phase III trial SECURE found the majority of s-ISZ measurements were within the range of 1–7 mg/L [ 23 ]. The median value in the present study was 4.3 mg/L and well within that range, the same as in other studies [ 7 , 8 , 9 , 12 , 17 , 24 , 25 , 26 ]. In the present study, the majority of the s-ISZ measurements were also within the recommended range, but for VRZ a third of TDM measurements were outside the recommended range, which is also in accordance with the literature [ 27 ].…”
Section: Discussionsupporting
confidence: 92%
“…Two patients had breakthrough fungal infections even with high levels of s-ISZ. Breakthrough fungal infections during ISZ prophylaxis or treatment have also been reported by others [ 7 , 8 , 9 , 10 , 11 , 32 , 33 ]. Breakthrough fungal infections during ISZ prophylaxis in hematological patients when s-ISZ was within the therapeutic range have also been observed [ 9 ].…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…At the moment, we routinely use posaconazole as antifungal prophylaxis, even when isavuconazole is usually better tolerated and has fewer interactions than other azoles. 43 Isavuconazole, however, may also worsen myelosuppression due to increased levels of VEN, despite being a moderate CYP3A4 inhibitor. So far, there is no evidence that the use of isavuconazole is preferable to posaconazole concomitantly with VEN.…”
Section: Discussionmentioning
confidence: 99%
“…Of 20 patients enrolled, 2 (10%) were considered as failure as they developed a possible fungal infection. A more recent open-label phase II study in AML and myelodysplastic syndrome (MDS) patients undergoing remission-induction therapy reported the development of b-IFD (2 probable-pulmonary aspergillosis-and 8 possible) in 10 (15%) of 75 enrolled patients while on ISV prophylaxis [24]. The possible explanations of these figures may be the advanced age of the population (median: 67 years) and the prolonged neutropenia, due to intensive chemotherapy or to venetoclax-based regimens.…”
Section: Isavuconazole In Hematological Patientsmentioning
confidence: 99%